Influence of Environmental, Social and Governance (ESG) in Investment Decision: Mediating Role of Investment Horizon - Chaudhary, Manoj Kumar; Dhungana, Madan; Chalise, Mahanada; Chaudhary, Rajesh Kumar; Paudel, Sujan Raj; Maharjan, Ojash (Nepal Journal of Multidisciplinary Research, 2024)
Purpose: The study investigates how Environmental, Social, and Governance (ESG) factors impact the investment choices made by individual investors in the stock market. Analyzing how ESG factors affect investors’ decisions is the primary goal, and evaluating how each ESG factor affects these decisions separately comes in second. In the relationship between ESG and investment decision-making, the study also looks at the function of investment horizon as a mediating variable. Methodology: This study adopts a descriptive and causal-comparative research framework utilizing the theory of planned behavior and stakeholder theory. Structured questionnaires collected primary data from 423 active stock market investors. Key variables were evaluated using a 5-point Likert scale. The data were then examined using AMOS version 26’s Structural Equation Modeling (SEM) to verify the theoretical relationships and investigate the interactions between the variables. Main Findings - The study found a strong and positive correlation between investment decision-making and Environmental, Social, and Governance (ESG) considerations. It also demonstrated the significant impact of ESG factors on investor behavior and decision-making by revealing how the investment horizon serves as a mediating factor, influencing the relationship between ESG factors and investment decisions. Applications - This study offers valuable insights for individual investors, aiding financial planning by identifying key ESG factors influencing investment decisions. It also provides guidance for SEBON and companies, supporting initiatives to promote ESG-focused investments, thereby aligning financial goals with sustainability objectives Novelty/ Originality - This study uses the investment horizon as a mediating variable to investigate how ESG factors affect investment decisions. It adds to conventional investment models by providing fresh perspectives on how long-term ESG factors affect financial planning. The study offers a framework for comprehending how portfolio strategies, particularly in emerging markets, are impacted by sustainable investment priorities.